2012
DOI: 10.1093/neuonc/nos299
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling is a key downstream mediator of MET signaling in glioblastoma stem cells

Abstract: These data suggest that Wnt/β-catenin signaling is a key downstream effector of MET signaling and contributes to the maintenance of GSC and GBM malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 70 publications
(48 reference statements)
1
86
0
Order By: Relevance
“…22,23 Crosstalk between EGFR, c-Met and Wnt/b-catenin is well documented in cancer cells, thereby linking b-catenin signaling and cell migration induced by growth factors. [24][25][26][27][28][29] Thus, stimulation of epithelial cells with EGF or HGF through the phosphorylation of cell adhesion proteins diminishes cell adhesion while promoting epithelial-mesenchymal transition (EMT). Phosphorylation of Y142 b-catenin by c-Met affects b-catenin interaction with a-catenin 30 and promotes a b-catenin switch from adhesive to transcriptional functions that facilitates promigratory phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Crosstalk between EGFR, c-Met and Wnt/b-catenin is well documented in cancer cells, thereby linking b-catenin signaling and cell migration induced by growth factors. [24][25][26][27][28][29] Thus, stimulation of epithelial cells with EGF or HGF through the phosphorylation of cell adhesion proteins diminishes cell adhesion while promoting epithelial-mesenchymal transition (EMT). Phosphorylation of Y142 b-catenin by c-Met affects b-catenin interaction with a-catenin 30 and promotes a b-catenin switch from adhesive to transcriptional functions that facilitates promigratory phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…33 Here we studied the role of b-catenin phosphorylated at Y142 (PY142) in cell invasion in GBM, a tumor in which total and dephospho S/T b-catenin (a classical Wnt transducer; hereon active b-catenin) have already received some attention. 20,34,35 We used GBM biopsies, cell lines and cell cultures established from tumoral tissue. Our findings identify a nuclear pool of PY142 b-catenin in GBM cells.…”
Section: Introductionmentioning
confidence: 99%
“…Then accumulating β-catenin translocates to the nucleus where it activates the transcriptional factors TCF/LEF then regulate target genes referring to cellular proliferation, differentiation, survival, and apoptosis [23]. Previous data reported that Wnt2 and Wnt5a was expressed in gliomas, and knockout of Wnt2 in human U251 glioma cells inhibited cell proliferation, invasive ability, and induces apoptosis [24]. Another experiment showed that the expression of Wnt5a was positively correlated with the proliferation of glioma cells in vitro.…”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…Several preclinical studies showed that MET is highly expressed in GSCs. 29,30,43 MET enhances GSCs via inducing the expression of reprogramming transcription factors and inducing differentiated cells to form multipotent stem cells. 43 Additionally, MET pathway inhibition in GSCs inhibits tumor growth and invasiveness both in vivo and in vitro.…”
Section: Cell Migration and Invasionmentioning
confidence: 99%